The strategy adopted by the Indonesian government contractors to maintain profit - Dwi Adi Sunarko, 1978-; Rosli Abdul Rashid, supervisor; Fakulti Alam Bina (2011)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan) - Universiti Teknologi Malaysia, 2011